The Serious Games of Participation: Civil Society Navigating the Peace Process Between the Colombian Government and the ELN - Fyr,Julia (2025)
This thesis provides an ethnographic analysis of civil society participation in the peace negotiations between the Colombian government and the insurgent group, the National Liberation Army (ELN). It examines how civil society actors navigated, engaged with, and attempted to influence the participatory process at the heart of the peace talks—negotiating internal and external power relations while imbuing their actions with narrative meaning. The study challenges the instrumental logic that often characterizes existing literature on civil society participation in peace processes, which tends to focus on whether and how inclusion contributes to sustainable peace. By shifting the lens toward the emic perspectives of participating citizens, this thesis offers an account of both the structural constraints that shaped their participation and the meanings and hopes that the process held for them. Situated within the field of Global Studies, the thesis represents an interdisciplinary approach that brings ethnographic reflection into dialogue with peace and conflict studies. It draws on Sherry Ortner’s practice theory and Cheryl Mattingly’s concept of emplotment to analyze how actors exercise agency and create meaning within constrained political contexts. The thesis concludes that civil society participants engaged with and sought to influence the peace process by contesting and renegotiating the structures, while tying their actions to a desired future imbued with meaning and hope. Participation was both a means and an end in itself, carrying both strategic and narrative potential. Rather than assuming a positive relationship between participation and peace, it proposes that participatory processes can reveal the conditions under which peace is made possible—or is foreclosed. The Colombian case contributes a nuanced understanding of participatory peace processes and highlights the tensions between global policy ideals and lived political realities on the ground. Word count: 20989
Keywords: Colombia; Civil Society; Participation; Peace processes; ELN; Agency; Narrative Theory